Plastic forms of architecture in Dynamo-Revit and GrasshopperRhino-Archicad - K. A. Shumilov; Yu. A. Guryeva (Омский научный вестник)
The paper presents the results of research on working with the Dynamo-Revit bundle and Grasshopper-Rhino-Archicad bundle when creating plastic architectural forms of complex geometry. Lotus, Canopy, Parametric Pavilion, Parametric Brick Wall, Small architectural form, Pergola, Beam structure objects are chosen as models for the researching. For the presented architectural objects the least resource intensive nodes and their bundles are selected. Nodes and their bundles in such a way as to optimally use the capabilities of programs and not overload computer resources are selected. The scripts developed in the Dynamo and Grasshopper programs for creating the presented models are briefly described. Explanations for the most significant fragments and full scripts used to work with models are given. The possibilities of the Dynamo and Grasshopper programs for visual (parametric) programming are briefly analyzed. Some possibilities of work of its bundle with Revit and Archicad are studied. The two-way work of the Dynamo-Revit bundle and Grasshopper-Rhino-Archicad bundle for import-export of the model is analyzed, including when changing the code to correct the model. It is advisable to continue working in this direction in order to obtain more concise and universal algorithms (chains of nodes) that allow varying the initial data and options for the shape of plastic architectural objects.